Determination of Financial Reporting Timeliness with Audit Delay as a Mediating Variable in Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2024 - Anggelica Ramadhani; Muhammad Rizal; Mohammad Chaidir (International Journal of Economics and Management Research, 2025)
This study aims to analyze the determinants of financial reporting timeliness with leverage measured by the Debt to Equity Ratio (DER) and profitability measured by Return on Assets (ROA) and to examine the role of audit delay as a mediating variable. A quantitative approach was used by utilizing secondary data obtained from the financial statements of energy sector companies listed on the IDX during the period 2021-2024. The research sample consisted of 136 observations analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. Empirical findings show that leverage and profitability do not directly affect the timeliness of financial reporting, indicating that the company's financial condition affects the length of the audit process. Audit delay has been proven to have a negative and significant effect on the timeliness of financial reporting, confirming that the longer the audit process (audit delay), the lower the level of reporting timeliness. The mediation test results show that audit delay is able to mediate the effect of leverage (DER) and profitability (ROA) on the timeliness of financial reporting. These findings reveal the role of audit delay as an intermediary mechanism in the relationship between company financial characteristics and the timeliness of financial reporting.